Facilitating design thinking to support food systems transformation. Dilemmas and strategies - Korner, Jana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Design thinking is becoming increasingly relevant for AR4D in the context of developing and scaling actionable innovations for food system transformation. However, to date there is limited experience in facilitating design thinking processes in different innovation spaces, i.e., with different multi-stakeholder groups that have different aims and different working styles. This working paper discusses learnings from four different design thinking initiatives that were designed and facilitated in the context of CCAFS and in collaboration with the CGIAR-GIZ Task Force on Scaling. Recommendations can be useful for further design thinking initiatives in the AR4D context, with regards to their set-up, potential dilemmas in their pathways through the problem-solution spaces, and the respective most suitable facilitation styles.